Inclusivity in the Labor Market - El-Ganainy, Asmaa (IMF Working Papers; Working Paper, 2021)
Labor earnings are the dominant income source for most individuals. Thus, an inclusive labor market is key for ensuring inclusive growth. In this paper we propose four principles that an inclusive labor market will embody: access, fairness, protection and voice. While measuring inclusivity presents challenges, we discuss how data can be used to shed light on the extent of inclusivity and document cross-country trends and stylized facts. We also discuss the role of policy in achieving an inclusive labor market, focusing on the need to rebalance growth; improve risk sharing; and fight discrimination. Several messages emerge. First, some policies entail a trade-off between the different dimensions of inclusivity. Second, it is important to view policies as a bundle, taking into account substitution and complementarities. Third, some policies are win-win, in the sense that they both increase inclusivity and improve overall efficiency.